The Effectiveness of the Role-Play Strategy in Developing Sixth Grade Students" Tendencies Towards English. - قاسم، فاتن محمد; الحسن، أحمد; إسماعيل، محمد (جامعة البعث, 2019)
الهدف من هذا البحث هو معرفة مدى فاعلية استراتيجية لعب الأدوار في تنمية الميول نحو اللغة الإنجليزية لدى طلاب الصف السادس. استخدمت الباحثة المنهج الوصفي والمنهج التجريبي، وذلك باستخدام مجموعة تجريبية ومجموعة ضابطة من طلاب الصف السادس للتحقق من صحة الفرضيات البحثية ورؤية فعالية استراتيجية لعب الأدوار في تنمية الاتجاهات نحو تعلم اللغة الإنجليزية. توصلت الدراسة إلى النتائج التالية: - هناك فروق ذات دلالة إحصائية عند مستوى الدلالة (0.05) بين متوسط درجات الطلاب في المجموعة التجريبية ومتوسط درجات الطلاب في المجموعة الضابطة. في مقياس ميل الطلاب إلى تعلم اللغة الإنجليزية، لصالح طلاب المجموعة التجريبية. - دور استراتيجية لعب الأدوار في تنمية الاتجاه نحو اللغة الإنجليزية على الأبعاد الثلاثة للمقياس كان كبير جدا. في ضوء نتائج الدراسة، اقترحت الباحثة ما يلي: - تشجيع استخدام استراتيجية لعب الأدوار في التدريس لأنها مهمة في تحفيز المتعلم. - دورات تدريبية للمعلمين لاستخدام استراتيجية لعب الأدوار في التدريس وإدراجه في المواقف التعليمية.
This research aims to know the effectiveness of the role-playing strategy in developing the tendencies towards English language among the sixth grade students. The researcher used the descriptive method and the experimental method using an experimental group and a control group for sixth grade students to validate research hypotheses and see the effectiveness of role-playing strategy in developing tendencies towards learning English. The study achieved the following results: -There are statistically significant differences at the significance level of (0.05) between the average of marks of the students in the experimental group and the average of marks of the students in the control group In the scale of students tendency to learn English, for the benefit of the students of the experimental group. -The role of role-play strategy in developing the tendency towards English language on the three dimensions of the scale is very large. In light of the results of the study, the researcher suggested the following: -Promoting the use of role-playing strategy in teaching because it's important in raising the motivation of the learner. -Holding training courses for teachers to use role-playing strategy in teaching and embedding it in educational situations. - Conducting further studies to determine the impact of role-playing strategy and its effectiveness in other study stages.
Keywords: السياسة التعليمية -- البرامج التعليمية -- طرق التدريس -- اللغة الإنجليزية -- الإستراتيجية التعليمية -- التعليم الإبتدائي -- طلاب المرحلة الإبتدائية